Part I—Theoretical Model for a Synchronous Thermal Instability Operating in Overhung Rotors - A. C. Balbahadur; R. G. Kirk (International Journal of Rotating Machinery)
Atheoretical model has been developed for a synchronous thermal instability that is caused by differential viscous shearing in bearings of overhung rotors. This model employs an unbalance threshold criterion for instability instead of utilizing a traditional frequency-domain stability analysis. The current model will be used to investigate several case studies for both plain and tilting pad journal bearing rotors in the second part of this article.